Sleep habits and Physiological Penal Gland Calcification (A Magnified Topographical Evolution Study) (Medico Legal Update, 2020)
Physiological pineal gland calcification is a frequent finding in computed tomography brain (CT) and its volume, shape and density is variable. Melatonin is the main product of pineal gland, and its role in sleep is well documented. Two-hundred ten patients were enrolled in this cross-sectional study done at Al-Sadder Medical City-Middle Euphrates Neuroscience Center (MENC)-Najaf; between February 2016 and December 2016. Several PGC parameters include PGC density, PGC volume and PGC cross sectional area were measured. We took their demographic information and their BMI and then questions about their sleep habits was applied to patients. the study group was (n=210) was referred for Brain CT for different reasons, mean age (43.9 years), of them male was (118), and female was (92) they represent (56.2% and 43.8%) respectively, that had insomnia was (85, 40.5%), the mean of pineal gland calcification volume (mm3), density (Hu) and cross sectional area (mm2) was (57.5, 131 and 12.5) respectively. In this study there were a strong correlation between PGC density and age, male gender and use of diazepam and Sleep with light on at night & decreased hours of night sleep showed statistically significant correlation with PGC volume and thus on PG function.